Métodos resolutivos para equações polinomiais do segundo grau em uma turma do ensino médio - TAVARES, Deivid Oliveira (2024)
This work addresses methods for solving quadratic equations in a high school class. The research seeks to investigate and analyze the relevance of the subject for students in a high school mathematics class and, concomitantly, present different methods that enable them to learn about the content, exploring concepts, examples for the use of resolution methods to degree two equations, covering the factorization, sum and product methods and the quadra tic formula “Bhaskara’s formula”. The main objective of this study is to explore different approaches to solving these equations, in order to help students understand and solve this type of mathematical problem more efficiently and effectively.